2021
DOI: 10.1155/2021/3997045
|View full text |Cite
|
Sign up to set email alerts
|

circHUWE1 Exerts an Oncogenic Role in Inducing DDP-Resistant NSCLC Progression Depending on the Regulation of miR-34a-5p/TNFAIP8

Abstract: Background. Circular RNAs (circRNAs) are reported as competing endogenous RNAs (ceRNAs) and play key roles in non-small-cell lung cancer (NSCLC) progression. Thus, this study was aimed at clarifying underlying molecular mechanisms of circHUWE1 in NSCLC. Methods. The quantitative real-time polymerase chain reaction (RT-qPCR) and western blot analyses were used for examining circHUWE1, microRNA-34a-5p (miR-34a-5p), and tumor necrosis factor alpha-induced protein 8 (TNFAIP8). IC50 of cisplatin (DDP) in A549/DDP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…This raises the possibility of a mechanism by which circHUWE1 functions to enhance the activity of HUWE1 protein. This is consistent with the conflicting literature suggesting different functional roles for circHUWE1 [29][30][31][32] . HUWE1 is an E3 ubiquitin ligase that regulates different proteins in a context specific manner.…”
Section: Core Essential Circrnassupporting
confidence: 92%
“…This raises the possibility of a mechanism by which circHUWE1 functions to enhance the activity of HUWE1 protein. This is consistent with the conflicting literature suggesting different functional roles for circHUWE1 [29][30][31][32] . HUWE1 is an E3 ubiquitin ligase that regulates different proteins in a context specific manner.…”
Section: Core Essential Circrnassupporting
confidence: 92%
“…Since the aforementioned study used different cells from the ones used in the present study, it is hypothesized that the different results may be caused by cell differences. In addition to ALDOA, other targets of miR-34a-5p, including TNFAIP8, flotillin-2, and hexokinase-1 have been revealed ( 18 , 40 , 41 ). Among them, Li et al reported that hexokinase-1 is also the key enzyme of glycolysis and participates in CRC progression ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notable, many circRNAs could serve as a sponge of miR-34a-5p, including circOgdh (also named mmu_circ_0000231) 176 , circMED12L 180 , circ_FURIN 181 , circ_CSNK1E 182 , circ0036602 183 , circ-LRP1B 184 , circHUWE1 185 , circITGA7 186 , circNFIX 187 , 188 , circRNA-CIDN 189 , circ_0009910 190 , circ_0039569 191 , hsa_circ_0018069 192 , suggesting that these circRNAs may promote lipid synthesis but suppress lipid accumulation by regulating miR-34a-5p/ACSL, ATGL, and ADAM10 axis.…”
Section: The Potential Role and Mechanism Of The Circrna/mirna Axis I...mentioning
confidence: 99%